Blow-Up fracture with concussion in a division I collegiate female soccer player - Seevers, K. M.; Stephenson, H. G.; Rosen, A. B. (International Journal of Athletic Therapy & Training, 2022)
The purpose of this case report is to present the case of a Division I collegiate female soccer player diagnosed with a blow-up fracture and a concussion. This athlete suffered from a blow-up fracture, a fracture of the superior orbital rim, which is less common than the inferior, blowout fracture. The uniqueness comes from a common mechanism, player-to-player contact, causing an uncommon fracture pattern and the athlete`s full, unrestricted, return to sport. Severity of these injuries can vary from very mild to very severe, and the treatment options are variable depending on the severity.